QUANTIFICATION OF THE INTERDEPENDENCE OF INNOVATION ABILITY AND COMPETITIVENESS OF THE SOUTHEAST EUROPEAN COUNTRIES - Cvetanović, Slobodan; Kostić, Aleksandar; Šušić, Vukašin (International Journal of Economic Practice and Policy, 2021)
Based on the data of the World Economic Forum, the individual impact of innovation capacity on the competitiveness of eleven countries in Southeast Europe in the period 2017-2019 was quantified by analyzing rank and index values and by using the method of correlation analysis. The obtained results confirmed the existence of a significant relationship between the ranks of innovation and competitiveness of the observed countries in the observed time interval. Also, the results of the research showed the existence of a direct link between the index of innovation ability and global competitivenss at a time when economic development is predominantly based on the so-called platform of the fourth industrial revolution. This implies the necessity of the existence of an efficient innovation policy in the countries of Southeast Europe, since the improvement of the country innovation capacity has a stimulating effect on the growth of their competitiveness.